Impact of cover crop on corn–soybean productivity and soil water dynamics under different seasonal rainfall patterns. (21st February 2020) - Yang, Wei; Feng, Gary; Read, John J.; Ouyang, Ying; Han, Jianjun; Li, Pinfang
Abstract: The effect of cover crop (CC) on soil water balance and agricultural production is closely related to rainfall amount and distribution in rainfed cropping systems. This study used the root zone water quality model, RZWQM2, calibrated and validated with 4‐yr field measurements to predict the effect of planting a winter wheat ( Triticum aestivum L.) CC in a no‐till rainfed corn ( Zea mays L.)–soybean ( Glycine max L.) rotation on soil water balance, crop yield, and grain water‐use efficiency (WUE) in northeast Mississippi. Seasonal rainfall for 80 consecutive years (1938–2017) was classified as 'wet, ' 'normal, ' and 'dry' years using frequency analysis, and the data sets matched chronologically to wheat, corn, and soybean growth periods were used as an input parameter in RZWQM2 simulations. During autumn and spring (early October to early April), the CC reduced deep drainage by 69 (11%), 53 (15%), and 51 mm (21%) in wet, normal, and dry years, respectively. Averaged across 40 yr, the CC decreased surface evaporation by 64 (32%) and 38 mm (24%) for corn and soybean growth periods, respectively. Wheat CC also improved soil water storage in early crop growth period during April–June in any of the three rainfall patterns. Regardless of rainfall patterns, the increase in WUE can be attributed to a decrease in evapotranspiration during cash crop period without sacrificing cash crop yield in the CC system. Introducing CC into cropping systems is beneficial to reduce annual deep drainage and evaporation while maintaining higher crop yields under different rainfall patterns.